Loss of Elp3 Impairs the Acetylation and Distribution of Connexin-43 in the Developing Cerebral Cortex - Laguesse, Sophie; Close, Pierre; Van Hees, Laura; Chariot, Alain; Malgrange, Brigitte; Nguyen, Laurent (Frontiers in Cellular Neuroscience, 2017)
The Elongator complex is required for proper development of the cerebral cortex. Interfering with its activity in vivo delays the migration of postmitotic projection neurons, at least through a defective α-tubulin acetylation. However, this complex is already expressed by cortical progenitors where it may regulate the early steps of migration by targeting additional proteins. Here we report that connexin 43 (Cx43), which is strongly expressed by cortical progenitors and whose depletion impairs projection neuron migration, requires Elongator expression for its proper acetylation. Indeed, we show that Cx43 acetylation is reduced in the cortex of Elp3cKO embryos, as well as in a neuroblastoma cell line depleted of Elp1 expression, suggesting that Cx43 acetylation requires Elongator in different cellular contexts. Moreover, we show that HDAC6 is a deacetylase of Cx43. Finally, we report that acetylation of Cx43 regulates its membrane distribution in apical progenitors of the cerebral cortex.